The Pricing of Best Efforts New Issues - SHERMAN, ANN GUENTHER (Journal of Finance, 1992)
ABSTRACT This paper offers an explanation for the underpricing of best efforts new issues and demonstrates that best efforts contracts allow issuers to use information from the market. If investors obtain information which indicates that a project will not be profitable, their demand will be low and the offering will be withdrawn. If this information is costly, investors will have to be compensated for its purchase through a lower offering price, which means that issuers will have to underprice. This result is consistent with the empirical observation that underpricing is considerably greater for best efforts than for firm commitment contracts.